La expresión rítmica musical como herramienta del desarrollo del lenguaje en estudiantes con necesidades educativas especiales en la escuela “Rosa Elena Velasteguí”, cantón Echeandía, provincia Bolívar; en el período 2011 – 2012 - Ortiz Andrade, Rocío Elizabeth (2012)
Identified the problem of not using the Dalcroze method in language development in students of the Special School "Rosa Elena Velasteguí" Canton Echeandia, we undertook a study to present the educational establishment in our research, a alternative solution that benefited students, parents, teachers, teachers, and community. The problem allowed us to raise the subject, it is determined as follows: "MUSICAL RHYTHMIC EXPRESSION AS A TOOL FOR DEVELOPMENT OF LANGUAGE STUDENTS WITH SPECIAL EDUCATIONAL NEEDS IN SCHOOL" ROSA ELENA Velastegui "CANTON Echeandia, Bolivar Province IN THE PERIOD 2011 - 2012" Then we continued with the description of the background, in which subject we recorded the problem in the institution justify our work degree, indicating in this part, the importance, relevance, need, originality, scientific novelty and feasibility. Formulate clear objectives and easily measured, as we hypothesize, "The Musical Rhythmic expression influences the development of language in students with Special Educational Needs in School" Rosa Elena Velasteguí "Echeandia Canton, Bolivar Province in the period 2011 - 2012 "which represents a response to the problem. From the hypothesis, we obtained the two variables: Independent: The musical and rhythmic expression Clerk: Language development, and these were operationalized in the appropriate boxes, facilitating further development of this survey was administered to teachers and parents family. In the theoretical framework of scientific theory, we recorded topics and subtopics related to the two variables, as well as in the Legal Framework, we note the articles of the Constitution, Education Law, Code of Children and Adolescents, which support our Work degree. Then proceeded to develop the conceptual theory and the theory Reference, with terms and phrases recorded in the scientific theory and research institution located in the social context, cultural and economic place. We select the most appropriate methods and techniques to effectively develop our work, we identify the universe with which we work, and process the data, following the established guidelines. Once we apply the survey to teachers and parents, and the observation sheet for children, tabulated data, we charts and graphs, then analyzing and making conclusions and recommendations and then we test the hypothesis. Finally we elaborate the proposal which tends to offer a range of strategies that helped the teachers with respect to language development of students with SEN, school through the application of rhythmic expression musical activities as a teaching strategy.